Kinesiology taping length and dynamic balance control in individuals with chronic ankle instability - Ruoni Yu; Xiaojian Shi; Zonghan Yang; Doa El-ansary; Roger Adams; Gordon Waddington; Jie Lyu; Jia Han (Scientific Reports)
Abstract To explore the effect of different lengths of kinesiology taping (KT) on dynamic balance control in individuals with and without chronic ankle instability (CAI). Thirty-one participants (16 CAI, 15 non-CAI) volunteered, and all of them were tested for dynamic balance with KT taping of varied strip lengths, in a random sequence, with taping conditions being: above-ankle taping (short taping), below-knee taping (mid taping), and above-knee taping (long taping). Dynamic balance was measured by the Y-Balance test (YBT) with three reaching directions; anterior (YBT-A), posteromedial (YBT-PM), posterolateral (YBT-PL), untaped at enrolment and immediately after each taping condition. Non-CAI participants consistently outperformed CAI all YBT measures made in the untaped condition (all p<0.05). Linear mixed model (LMM) analysis suggested there were significant KT-Group interactions reflecting reducing inter-group difference as tape length increased for YBT-C (F(3, 29) = 5.599, p = 0.016, ES = 0.104), YBT-PM (F (3, 29) = 3.53, p = 0.018, ES = 0.102) and YBT-PL (F (3, 29) = 2.72, p = 0.049, ES = 0.008), but not YBT-A (F (3, 29) = 1.44, p = 0.236). Paired t-tests suggested that in the CAI group, compared to the untaped condition, YBT-PM scores increased in all taping conditions, with mean difference (MD) from 3.5 to 7.0% (t = 2.17–5.17, p = 0.00-0.046, 95%CI = −9.83, −0.07), whereas YBT-C (MD = 4.2%, t = 1.03, p = 0.001, 95%CI = −6.36, −1.97) and YBT-PL scores (MD = 5.3%, t = 3.9, p = 0.001, 95%CI = −8.18, −2.41) increased only in the long-taping condition. KT taping can improve dynamic balance for individuals with CAI to a level of those without CAI. Longer KT taping seems to show superior effects. However, individuals without CAI may not benefit from KT taping when performing a dynamic balance task.